Factors Correlated with 21st Century Learning Skills of Nursing Students, Naresuan University - Kuntakalung, Rossarin; Khamthawon, Krittphat; Yaithin, Kittiya; Panboot, Nattakit; Nualkam, Nitchanan; Loisak, Thanyalak; Kaeorat, Phornsiri; Tomak, Sasikan; suwannakeeree, wongduan (NU Journal of Nursing and Health Sciences, 2022)
The objectives of this descriptive correlational research were to study 1) the factors of learner, instructor, teaching and learning management, and supporting and 2) the 21st century learning skills reported by nursing student, and 3) determine the relationship between those factors and the 21st century learning skills of nursing students, Naresuan University. The study sample was composed of 159 nursing students in the 3rd and 4th year levels in the academic year 2021. The research instruments were the questionnaires of the factors; learners, instructors, teaching and learning management, and supporting, and the 21st century learning skills. The content validity indexes of the questionnaires were 1.0, 0.97, 1.0, 1.0 and .99, respectively. The Cronbach’s alpha coefficients of the questionnaires were .83, .92, .93, .91 and .93, respectively. Data were analyzed by descriptive statistics and Spearman rank correlation coefficient. The result revealed that the overall 21st century learning skills of nursing students were at the high level ( = 4.16, S.D. = .40). The nursing students reported the high level of all factors; learner, instructor, teaching and learning management, and supporting ( = 4.21, S.D. = .46, = 4.16, S.D. = 4.9, = 4.11, S.D. = .48 and = 3.96, S.D. = .59, respectively). All the factors had positive relationship and statistically significant (p < .001) with 21st century learning skills of nursing students. The learner factor had high relationship (r = .73), and instructor, teaching and learning management, and supporting factors had moderate relationship (r = .62, .61 and .57, respectively).